ISTIQAMAH TERHADAP SYARI'AT AGAMA (Studi Psikologi Agama) - Burdjani As. (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2007)
Ltiqdhrh k dne's .ondinon oi ad effon tlr dtibntely keep folowing thc $a) of relsion s guided bt' AIah SwI. Literaly, this word mcms srraight, detemi,ed, dd consisrent.',\s a religious pe6oq, someone musr be obedimt to fie law ot l!1s religion and folow the way guided by Allah. htiquah is tne otposne olhi?o.nsy. -\ h}?ocri p^on is tror consisrenr berwee. vhat is in hi3 hcart. his vords, and his acts, likes ro lie, never Leeps the promis, od betays odefs tn,$. Lr?22,.4 is able to prevent a peaon from dohg e'{ especidly ddiat io .Ul2h aqcr hc acknoNledges his fdrlt. A personsao is isiiqaruh tovards laws of .elgon 6 honest. nght, md ncntally healthy. Psychologlcaly, a person who is ncrtal hcaldT has m $iliq, to djust with hioself. othd people, md rhe slfosdhg where he Lves." Io other woids, he will be .ble to .cheve L@ooy ia hls so , also able to face the exirtinA problms, dd positivery feel the bappiness." lstqdrh is x chd"cter vhich oust be Lept by every fairhtul peoplc, 'tu md vonan, because with this charactc! a persd wifl bc able to kep the Is]anic tea.hinss wherEi he is.,